PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS III SDN 3 ANCARAN - Salwa Regina Anggraini; Riqi Taufikurohman; Seli Selvia; Ina Setiawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of the Problem Based Learning (PBL) model on the learning outcomes of third-grade students in Pancasila Education at SDN 3 Ancaran. The study used a quantitative approach with a pre-experimental method employing a One Group Pretest-Posttest Design. The subjects of the study consisted of 20 third-grade students selected using a saturated sampling technique. Data were collected through pretest and posttest essay tests to measure students’ cognitive learning outcomes. Data analysis was conducted using descriptive statistics, normality tests, and the Wilcoxon Signed Rank Test. The results showed that students’ learning outcomes improved after the implementation of the Problem Based Learning model. The normality test indicated that one of the data sets was not normally distributed; therefore, hypothesis testing was continued using the Wilcoxon Signed Rank Test. The hypothesis test showed a significance value lower than 0.05, indicating that there was a significant effect of the Problem Based Learning model on students’ learning outcomes in Pancasila Education. The findings suggest that the Problem Based Learning model can create more active, meaningful, and student-centered learning in elementary schools.